Perempuan dalam Panggung Dakwah Islam: Kajian Tematik Hadis dan Relevansinya di Era Kontemporer - Khairun Nada; Zesar Rahmat Syafi’e; Hanief Monady (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Islamic da'wah plays an important role in guiding humanity towards achieving salvation in both this world and the hereafter. Since the early spread of Islam, women have been involved in da'wah through the gatherings held by the Prophet Muhammad SAW. Although there has been debate over the role of women in da'wah, women are increasingly active in spreading Islamic teachings, both in public spaces and through digital media. This research analyzes hadiths related to the role of women in da'wah, using a qualitative approach based on library research. The focus of this study is to identify key themes in hadiths that support or limit the role of women, as well as how classical and contemporary scholars interpret these hadiths. Additionally, this study examines the role of women in da'wah in the contemporary era, both through social media and academic spaces, as well as the challenges faced by female preachers and analyze in terms of gender equality. In conclusion, despite differing views among scholars, women have an important role in Islamic da'wah, which remains relevant in the modern era, supported by inclusive da'wah strategies based on maqashid sharia.